PERMASALAHAN YANG MUNCUL AKIBAT PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN - Wiwi Idawati (Jurnal Akuntansi Bisnis, 2017)
Good governance requires a paradigm shift critical of the Government of the old system that is too centralized, with the central Government very strong in the determination of the policy. The new paradigm requires a system capable of reducing dependency and even eliminate dependency on local governments to the central government, as well as to empower local governments to be able to compete both regionally, nationally and internationally. Responding to the new paradigm, the government provides the widest possible autonomy to the region which aims to enable regions to manage and regulate their own household so efficiently and effectively in governance and development as well as within the framework of services to the community. The implementation of regional autonomy implemented by giving broad autonomy and proportional to the area are realized with the arrangement, distribution and utilization of national resources and a fair fiscal balance between central and local governments.Kata Kunci: Standar Akuntansi pemerintah, Good Governance.